2009
DOI: 10.1104/pp.109.139683
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphofructokinase B-Type Carbohydrate Kinase Family Protein, NARA5, for Massive Expressions of Plastid-Encoded Photosynthetic Genes in Arabidopsis    

Abstract: To date, there have been no reports on screening for mutants defective in the massive accumulation of Rubisco in higher plants.Here, we describe a screening method based on the toxic accumulation of ammonia in the presence of methionine sulfoximine, a specific inhibitor of glutamine synthetase, during photorespiration initiated by the oxygenase reaction of Rubisco in Arabidopsis (Arabidopsis thaliana). Five recessive mutants with decreased amounts of Rubisco were identified and designated as nara mutants, as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 79 publications
1
24
0
Order By: Relevance
“…In this study, we aimed to detect total mutations in the mutants without backcrossing. Despite this restriction, candidate mutations for those responsible for our focused mutant phenotypes ( Figure S1) were found in the mutated genes NARA5 (Ogawa et al, 2009) in Ar-57-al1; ASYMMET-RIC LEAVES1 (Byrne et al, 2000) in Ar-365-as1, and CYP85A2 (Kim et al, 2005) in Ar-443-as1. For forward genetics strategies in radiation-induced mutants identification of responsible genes will be made even more rapidly and efficiently by resequencing bulked segregants from a backcrossed population and detecting homozygous mutations in the genetic regions using the three algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aimed to detect total mutations in the mutants without backcrossing. Despite this restriction, candidate mutations for those responsible for our focused mutant phenotypes ( Figure S1) were found in the mutated genes NARA5 (Ogawa et al, 2009) in Ar-57-al1; ASYMMET-RIC LEAVES1 (Byrne et al, 2000) in Ar-365-as1, and CYP85A2 (Kim et al, 2005) in Ar-443-as1. For forward genetics strategies in radiation-induced mutants identification of responsible genes will be made even more rapidly and efficiently by resequencing bulked segregants from a backcrossed population and detecting homozygous mutations in the genetic regions using the three algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…C. melo and Nicotiana tabacum (ecotype SR1) were grown under the same conditions, as for the wild watermelon, and fully-expanded fourth leaves were used for protein extraction. Arabidopsis thaliana (ecotype Col-0) was grown on Murashige and Skoog nutrient agar plates for 3 weeks, as described previously, 23) and the rosette leaves were used for protein extraction.…”
Section: Methodsmentioning
confidence: 99%
“…However, the function of s factors is likely to be redundant, and a specific one(s) for rbcL has not been reported. Protein factors such as CSP41 (Bollenbach et al, 2009) and NARA5 (Ogawa et al, 2009) have been reported to be involved in the transcription of rbcL via PEP in Arabidopsis, but they also affect the mRNA levels of genes for other chloroplast photosynthetic components. Thus, a pathway of specific transcriptional activation of rbcL has not yet been clarified.…”
Section: The Availability Of Rbcs Up-regulates Transcript Levels Of Rbclmentioning
confidence: 99%